2014
DOI: 10.1155/2014/796121
|View full text |Cite
|
Sign up to set email alerts
|

Occult Hepatitis B Virus Infection among HIV Positive Patients in Nigeria

Abstract: HIV has been known to interfere with the natural history of hepatitis B virus (HBV) infection. In this study we investigate the prevalence of occult hepatitis B virus infection (OBI) among HIV-infected individuals in Nigeria. Overall, 1200 archived HIV positive samples were screened for detectable HBsAg using rapid technique, in Ikole Ekiti Specialist Hospital. The HBsAg negative samples were tested for HBsAg, anti-HBc, and anti-HCV by ELISA. Polymerase chain reaction was used for HBV DNA amplification and CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 11 publications
2
14
0
2
Order By: Relevance
“…(15) Anti-HBc was detected in 29.20% and 27.3% of HIV infected patients in Nigeria and Brazil respectively. (17,16) Anti-HBc was the sole HBV marker in 35 (17.77%) HIV patients, which is close to 17.50% (71 out of 405) and the 16% (38 out of 240) reported in Italy and Boston, respectively. (18,19) Isolated anti-HBc was detected in 12.7% in the study carried out by Aly (15) However, this percent is lower than what has been described in previous studies of HIV-positive patients, namely; the 26.80% detected in India, (20) and the 28.30% in Taiwan.…”
Section: Discussionsupporting
confidence: 63%
“…(15) Anti-HBc was detected in 29.20% and 27.3% of HIV infected patients in Nigeria and Brazil respectively. (17,16) Anti-HBc was the sole HBV marker in 35 (17.77%) HIV patients, which is close to 17.50% (71 out of 405) and the 16% (38 out of 240) reported in Italy and Boston, respectively. (18,19) Isolated anti-HBc was detected in 12.7% in the study carried out by Aly (15) However, this percent is lower than what has been described in previous studies of HIV-positive patients, namely; the 26.80% detected in India, (20) and the 28.30% in Taiwan.…”
Section: Discussionsupporting
confidence: 63%
“…In a study of HBV occult infection among HIV positive patients, Opaleye et al found HBV DNA in 21/188 (11.2%) of patients without detectable HBsAg [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, this bias is somewhat balanced by missing the diagnosis of occult HBV infection (undetectable HBsAg in serum with the presence of HBV DNA), with proportions of occult HBV infection ranging from 3% to 11% in people with HIV. 43,44 Second, HCV diagnosis was based on antibodies, not RNA. With the high prevalence of interleukin 28B genotype CC in Asia, 45 patients who might have cleared the infections were included in the HCV group, overestimating the prevalence of HCV infection.…”
Section: Discussionmentioning
confidence: 99%